Climate and biocrust types jointly regulate soil multifunctionality and quality in drylands: evidence from the Gurbantunggut Desert - Li, Yonggang; Gao, Yingjie; Huang, Yunjie; Lu, Yongxing; Yin, Benfeng; Zhou, Xiaobing; Yu, Hao; Zhang, Yuanming (Frontiers in Plant Science, 2026)
Soil multifunctionality (SMF) and the soil quality index (SQI) are essential indicators of soil function, productivity, and health. Additionally, the spatial variability of soil multifunctionality (SVM) signifies soil heterogeneity. Biological soil crusts (Biocrusts) can affect these indicators. However, there is little information about the role of biocrusts in regulating the response of multiple ecosystem functions to climate change. We evaluated the relative importance of climate, soil environment, and biocrusts variables as drivers of SMF, SQI, and SVM at 74 sites in the Gurbantunggut Desert. Soil SMF, and SQI increase with the coverage of lichen and moss crust. Biocrusts index, SMF and SQI increase with an increase in the mean annual temperature. Biocrusts index, SMF and SQI increase first with an increase in mean annual precipitation (MAP)< 163 mm and then decrease. SVM display a significant decreasing trend with the increase of MAP. The structural equation model (SEM) demonstrate that the spatial distribution can significantly influence the biocrusts, soil SQI and SVM. Biocrusts has a significant positive influence on soil SMF (0.47)and SQI (0.31). Soil SMF has a significant negative effect on SVM (-0.50), and SQI (0.59) has a significant positive effect. We provide the first quantitative evidence that biocrust type and a 163 mm precipitation threshold govern SMF through opposing direct vs. indirect temperature pathways, offering a predictive rule-of-thumb for dryland management under climate change. The findings contribute decidedly to our understanding of the patterns and mechanisms driving SMF, SQI, and SVM in drylands, which is important for predicting changes in ecosystem function under climate change.